(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The culture of behavior is an integral part of human culture; it acts as an external expression of the spiritual wealth of the individual, his inner world. This is a set of forms of everyday human behavior (in work, everyday life, communication), in them the external expression of the moral and aesthetic norms of his behavior is manifested. They especially highlight the culture of speech, the ability to competently, clearly and beautifully express one’s thoughts without using vulgar expressions, etc.